2019
DOI: 10.1002/jhet.3644
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel 4‐Substituted Coumarins, Docking Studies, and DHODH Inhibitory Activity

Abstract: Coumarins are the important class of naturally occurring heterocyclic compounds. Activities like antioxidant, antibacterial, anti‐inflammatory, and anticancer have been reported for coumarin derivatives. Present work details the synthesis of substituted coumarin‐4‐pyrrolones as well as coumarin‐4‐acetyl amino acids and their DHODH inhibitory activity, which is a dual target for malaria and cancer. Coumarin‐4‐acetic acids (2a–c) were coupled with different methyl esters of α‐amino acids (3) giving rise to corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…By using standard methods, we synthesized two coumarin derivatives viz, 3-[2-Oxo-2-(2-oxo-2H-chromen-3-yl)-ethylidene]-1,3dihydro-indol-2-one (3OCE) and 3-[2-Oxo-2-(3-oxo-3H-benzo[f]chromen-2-yl)-ethylidene]-1,3-dihydro-indol-2-one (3OBC) [63,65]. Solvents of different dielectric constant such as methanol (ML), acetonitrile (AN), ethanol (EL), dimethyl formamide (DMF), dimethyl sulphoxide (DMS), tetrahydrafuran (THF) and ethyl acetate (EA) are all of spectroscopic grade.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…By using standard methods, we synthesized two coumarin derivatives viz, 3-[2-Oxo-2-(2-oxo-2H-chromen-3-yl)-ethylidene]-1,3dihydro-indol-2-one (3OCE) and 3-[2-Oxo-2-(3-oxo-3H-benzo[f]chromen-2-yl)-ethylidene]-1,3-dihydro-indol-2-one (3OBC) [63,65]. Solvents of different dielectric constant such as methanol (ML), acetonitrile (AN), ethanol (EL), dimethyl formamide (DMF), dimethyl sulphoxide (DMS), tetrahydrafuran (THF) and ethyl acetate (EA) are all of spectroscopic grade.…”
Section: Methodsmentioning
confidence: 99%
“…The crystal structure of galactose binding 10. These parameters infer that the coumarin compounds will bind strongly with periplasmic proteins of the blood [64,65].…”
Section: Analysis Of Molecular Dockingmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, antifungal experiments have shown that these compounds have moderate or even excellent antibacterial activity against common clinical pathogens. Further, Patagar et al ( 2019 ) designed and synthesized substituted coumarin-4-acetyl amino acids and determined their inhibitory activity against DHODH, a dual-target compound for malaria and cancer. The DHODH inhibitory activity of the newly synthesized compound was then determined.…”
Section: Application Of Amino Acids In the Structural Modification Of Natural Productsmentioning
confidence: 99%
“…The mechanism of the interaction between boronic acid and sugars through intermediates tetrahedral boronate 2 and boronate esters 3 and 4 is shown in Scheme 1. [ 2–4,19–41 ]…”
Section: Introductionmentioning
confidence: 99%